Effect of Single-Use, Laser-Cut, Slow-Flow Nipples on Respiration and Milk Ingestion in Preterm Infants - McGrattan, Katlyn E. (Am J Speech Lang Pathol, 2017)
PURPOSE: Single-use, laser-cut, slow-flow nipples were evaluated for their effect on respiration and milk ingestion in 13 healthy preterm infants (32.7–37.1 weeks postmenstrual age) under nonlaboratory, clinical conditions. METHOD: The primary outcomes of minute ventilation and overall milk transfer were measured by using integrated nasal airflow and volume-calibrated bottles during suck bursts and suck burst breaks during slow-flow and standard-flow nipple bottle feedings. Wilcoxon signed-ranks tests were used to test the effect of nipple type on both outcomes. RESULTS: Prefeeding minute ventilation decreased significantly during suck bursts and returned to baseline values during suck burst breaks across both slow-flow and standard-flow nipples. No differences were found in minute ventilation (p > .40) or overall milk transfer (p = .58) between slow-flow and standard-flow nipples. CONCLUSIONS: The lack of difference in primary outcomes between the single-use slow-flow and standard-flow nipples may reflect variability in nipple properties among nipples produced by the same manufacturer. Future investigations examining the effect of both single-use and reusable nipple products are warranted to better guide nipple selection during clinical care.